The Procedural Model of Criminal Prosecution in the Modern Criminal Procedure Legislation of the Republic of Kazakhstan - SULTANOV, Nurbolat (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
This article is dedicated to the study of the criminal prosecution model, developed after the enforcement of the Criminal Procedure Code of the Republic of Kazakhstan (CPC RK). It is often noted in the scientific papers, that the new vision of the criminal prosecution function in the CPC RK is related to the idea of internationalization of the domestic criminal proceedings. The current CPC RK contains a lot of novels, allowing to refer to a qualitatively new model of criminal prosecution, which differs greatly from the model, effective in the legislation of previous years. The aim of the study is to develop the author's model of the national criminal prosecution and to determine the ways of its optimization (improvement) based on the said model. The analysis of these novels governing the criminal prosecution in the system of modern pre-trial proceedings is performed. Their positive impact is noted, especially in terms of the organization of the criminal prosecution, despite all quite natural technical roughness and flaws that are not too difficult to remove. It is also noted that the legislator has managed to depart from the common Soviet procedural hangover toward to the national institutional model of criminal procedure of the new kind, toward to a truly modern, European-style criminal procedure model. It is concluded that the modern Kazakhstan legislator in the course of development of the Criminal Procedure Code preferred the competitive model, tending to the continental criminal procedure. It is emphasized that the current model of the criminal prosecution should ensure the rights and the freedoms of the participants in the criminal proceedings. It is through the adaptation of the Western legal technology that the concept of combating the crime, aimed at the European integration, should be created. At the same time, the new, ill-considered, hasty, distinctive innovations of the criminal and criminal procedural legislation under the slogans of the humanization of the attitude to the criminals should be avoided.
Keywords: criminal prosecution; the type of the criminal procedure; adversarial system; prosecution; preliminary investigation